Pengabdian masyarakat dalam pengelolaan Sampah serta memberikan petunjuk jalan untuk menuju Wisata Mangrove - Tyasmiarni Citrawati (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2022)
Bangkalan Regency has a lot of natural tourism potential. One of them is mangrove ecotourism in Tajungan Village, which is located in Kamal District, Bangkalan Regency, Tajungan Village. The development of mangrove ecotourism is still 25% but this tour has been opened by village officials. There are many shortcomings in the mangrove tourism, one of which is the access road that is not known by tourists to the mangrove tourism. Making plans to show road access to mangroves is made to provide guidance to tourists to mangrove tourism. The main goal is part of the Tri Dharma of Higher Education and to find solutions related to waste in mangrove tourism so that tourism looks natural and has added value, knows the perceptions, participation, and aspirations of stakeholders to develop strategies in developing ecotourism to be much more advanced